Pengaruh Pendekatan Concrete Representational Abstract (CRA) Berbantu Alat Peraga terhadap Kemampuan Representasi Matematis Siswa - Normalita Isnaeni; Sessu, Andi; Hadi, Windia (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
This study aims to determine whether or not there is an influence of the Effect of Concrete Representational Abstract (CRA) Assisted Teaching Aids in the Framework of Space Building Against the Mathematical Representation Ability of Junior High School Students on Flat Side Space Building Materials. The research method is quantitative research and use a quasi-experimental with Post-Test Only Design, Non Equivalent Group Design. The study population is all of eight grade students’ at 180 Junior High School Jakarta in the second semester of the academic year 2018/2019. The samples of this study are 64 students’ of class VIII-E and VIII-F. The sampling technique using is a Cluster Random Sampling technique. This study used a data collection method by used is the instrument test of mathematical problem-solving ability. The instrument first tries at Junior High School 222 Jakarta for 60 students’ in class IX-B and IX-C. This study used tested normality, the obtained data normally distributed. Hence, hypothesis testing was using the F test with Z cal is 5,0198 which resulted in the rejection of H0 in significance level about 5% with Effect Size of 1,479 is high. Therefore, this study concluded that there is The Effect of Concrete Representational Abstract (CRA) Approach Aided by the Framework of Space Building Framework on the Mathematical Representation Ability of Junior High School Students on Flat Side Space Building Materials with testing criteria is high.